Origines et évolution du droit québécois de l’absence : de l’existence incertaine aux présomptions de vie et de mort - Cloutier, Étienne (McGill Law Journal, 2017)
This article begins with a review of the first manifestations of the civilian institution of absence in Roman law and the French Napoleonic Code.  It then retraces the historical and conceptual origins of Quebec’s law of absence detailing its evolution from the Civil Code of Lower-Canada to the Civil Code of Quebec.